2004
DOI: 10.1113/expphysiol.2003.002640
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between nitric oxide and superoxide on the neural regulation of proximal fluid reabsorption in hypertensive rats

Abstract: This study investigated the role of nitric oxide (NO) and superoxide anions in modulating the renal nerve-dependent increases in proximal tubular fluid reabsorption (Jva). Renal nerve stimulation at 0.75 and 1.0 Hz (15 V, 0.2 ms) in anaesthetized Wistar rats had no effect on glomerular filtration rate but decreased urine flow and sodium excretion in a frequency-related manner, reaching 39 and 49% at 1.0 Hz, respectively (P < 0.01) and increased Jva by 11 and 31% (P < 0.01). In the stroke prone spontaneously hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…J v was also lower in adult stroke-prone SHR4, compared to WKY. This may be related to increased reactive oxygen species (ROS), since direct microperfusion of reducing agents corrected this dysfunction4. The SHR is indeed an established model of oxidative stress, with elevated superoxide levels and NADPH oxidase expression in both vascular and renal tissue 5.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…J v was also lower in adult stroke-prone SHR4, compared to WKY. This may be related to increased reactive oxygen species (ROS), since direct microperfusion of reducing agents corrected this dysfunction4. The SHR is indeed an established model of oxidative stress, with elevated superoxide levels and NADPH oxidase expression in both vascular and renal tissue 5.…”
Section: Introductionmentioning
confidence: 82%
“…For example, in 7 and 12 week old SHR, at a time when hypertension was established, baseline J v in the proximal tubule was lower compared to WKY3. J v was also lower in adult stroke-prone SHR4, compared to WKY. This may be related to increased reactive oxygen species (ROS), since direct microperfusion of reducing agents corrected this dysfunction4.…”
Section: Introductionmentioning
confidence: 95%
“…We previously showed that SHR PTE cells have an enhanced sensitivity to H 2 O 2 -induced stimulation of Cl -/HCO 3 -exchanger activity when compared with WKY PTE cells [20] while previous studies on the effect of ROS on proximal tubule transport involved superoxide [12,13]. In an attempt to determine the mechanisms responsible for differences in H 2 O 2 sensitivity between renal PTE cells from hypertensive and normotensive rats, the present study examined the role of the major mitogen-activated protein kinase (MAPK) signalling pathways.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of ROS in renal proximal tubule is not well established. Indeed, superoxide has been reported to decrease renal proximal tubule transport by inhibiting NHE3 activity in the adult SHR [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although increased proximal tubular fluid and sodium reabsorption could contribute to sodium retention and development of hypertension in SHR, the overactive sodium transport is not seen in older SHR (4). Also, there are reports that either failed to show difference in sodium reabsorption between adult SHR and Wistar-Kyoto rats or observed reduced proximal tubular fluid reabsorption and NHE3 activity in SHR (4,23,31). The exact mechanisms for these discrepancies are not clear; however, it is possible that age or strain difference could play an important role in renal sodium regulation.…”
Section: Discussionmentioning
confidence: 82%